X-Ray Crystallography - James, R. W. (Monographs on physical subjects, 1930)
Crystal form and the space lattice - The crystal lattice as a diffraction grating - The symmetry of crystals and its determination by means of X-Ray - The intensities of X-Ray spectra - Types of crystal structure.